What's New in Pediatric Orthopaedic Trauma: The Upper Extremity. Issue 4 (April 2020) - Hosseinzadeh, Pooya; Rickert, Kathleen D.; Edmonds, Eric W.
Abstract : Background: Upper extremity fractures are the most common fractures in children. Many high-quality studies have been reported regarding operative and nonoperative treatment of different upper extremity fractures in children. This review will summarize the literature on 4 major upper extremity fractures in children over the past 5 years. Methods: PubMed and Embase databases were queried for publications in the English language on supracondylar humerus (SCH) fractures, lateral humeral condyle fractures, medial epicondyle fractures, and clavicle fractures from January 1, 2013 until November 1, 2018. Papers believed to yield significant findings to our profession were included in this review. Results: A total of 1150 studies were related to the search terms, and after cursory assessment, the authors elected to fully review 30 papers for this publication: 12 related to SCH fractures, 10 related to lateral condyle humerus fractures, 3 related to medial epicondyle humerus fractures, and 5 involving clavicle fractures. The level of evidence for these studies was either level III or IV. Conclusions: SCH fractures are increasingly being treated at trauma centers or pediatric hospitals in the United States. The rate of open reduction in this fracture type is decreasing overall, but the flexion type SCH fractures (especially in the setting of ulnar nerve injury) continue to be at increased risk of requiring open reduction. There has been a paradigm shift in the treatment of lateral condyle humerus fractures, wherein authors have demonstrated successful management with closed reduction and percutaneous pinning when an adjunct arthrogram is performed demonstrating articular congruity. More studies are needed to find the optimal treatment for displaced medial epicondyle and clavicle fractures in adolescents, as results to date do not necessarily mirror those seen in the adult population. Level of Evidence: Level IV.